Socio-Economic Vulnerable Women and the Influence on Children Caring in Garut District - Joko Susilo Raharjo; Hadi Prabowo; Sampara Lukman (GoAcademica Research & Publishing, 2021)
The research aimed to assess women's attitudes toward children from low and high socio-economic backgrounds. The study sample included 300 children, 143 women and 157 boys. This research used a quantitative method with a descriptive-analysis approach. Female children were given